2020
DOI: 10.3389/fsurg.2020.578565
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Onlay Mesh Implantation During Definitive Fascial Closure After Open Abdomen Therapy (PROMOAT): Absorbable or Non-absorbable? Methodical Description and Results of a Feasibility Study

Abstract: Introduction: Incisional hernia development after open abdomen therapy (OAT) remains a common complication in the long run. To demonstrate the feasibility, we describe our method of prophylactic onlay mesh implantation with definitive fascial closure after open abdomen therapy (PROMOAT). To display the feasibility of this concept, we evaluated the short-term outcome after absorbable and non-absorbable synthetic mesh implantation as prophylactic onlay.Material and Methods: Ten patients were prospectively enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Furthermore, the large screened to randomized patient ratio implies a high risk of selection bias and limits the external validity of our results. Adding to that, the follow-up time of 1 year for incisional hernia might not be absolutely representative of the incisional hernia rates occurring after emergency midline laparotomy [ 41 , 42 ]. More than half of all screened patients fulfilled the exclusion criterion of previous laparotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the large screened to randomized patient ratio implies a high risk of selection bias and limits the external validity of our results. Adding to that, the follow-up time of 1 year for incisional hernia might not be absolutely representative of the incisional hernia rates occurring after emergency midline laparotomy [ 41 , 42 ]. More than half of all screened patients fulfilled the exclusion criterion of previous laparotomy.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, these patients are the ones that may profit the most from strategies to reduce wound complications which are very common in these cases. Potentially, while not the subject of this review, the use of barbed sutures ( 50 ) as well prophylactic mesh implantation have shown promising first results in such settings ( 55 ) with the updated guidelines of the European Hernia Society suggesting the latter in specific high risk situations. Further research, both primary and clinical, is needed to prevent post laparotomy wound complications in both elective and emergency settings such as emergency laparotomy and open abdomen treatment.…”
Section: Discussionmentioning
confidence: 99%
“…But using vacuum-assisted wound closure and mesh-mediated fascial traction (VAWCM) as a measure to dynamically approximate and close the rectus abdominis fascia with staged surgical procedures and a visceral protective layer to the vacuum dressing to avoid entero-atmospheric fistulas, morbidity of that procedure will be much lower than 20 years ago ( Beltzer et al, 2016 ; Coccolini et al, 2018 ; Schaaf et al, 2020 ; Weigelt and Kingman, 1988 ; Willms et al, 2015 , 2020 , 2022 ).…”
Section: Introductionmentioning
confidence: 99%